2003
DOI: 10.1159/000070384
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Exon 11 of the c-kit Gene in a Myogenic Tumor and a Neurogenic Tumor as Well as in Gastrointestinal Stromal Tumors

Abstract: Background/Aims: Gain-of-function mutations in exons 9, 11 and 13 of the c-kit gene in gastrointestinal stromal tumors (GISTs) have been identified, and it has been reported that the prognosis is worse for patients with mutation-positive GISTs than for those with mutation-negative GISTs. We studied c-kit mutations in gastrointestinal mesenchymal tumors. By chance, the c-kit mutation in exon 11 was found in myogenic and neurogenic tumors as well as in GISTs. Furthermore, we studied the clinical prognostic utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In the present study heterogeneouspoint mutations in AML patients were observed,some of which were and were not previously reported.In 19 of the 31 AML patients 20 point mutations wereobserved; a point mutation at Lys550Asn in 1 patientand at Ile571Leu in 2 other patients were previouslyreported [29-32]. Mutation at codon 582 (Trp582Tyrand Trp582His) was reported by Tae Won Kim et al [30]and Ying-Yong Hou et al [17] reported Trp582Try andTrp582Gln; however, in 3 of the present studied patientsthere was a different substitution in the same codon inwhich tryptophan was replaced by serine (Trp582Ser).Mutations at codons Tyr568Asp, Ile571Thr, Thr574Tyr,Gln575Ile, Tyr578Phe, Asp579Gln, Asp579Pro,His580Leu, His580Tyr, His580Pro, Arg586Trp,Arg586Ile, Arg586Phe, Arg586Asp, Asn587Glu,Asn587Pro, Asn587His and Arg588Phe, Arg588Tyr, andArg588Lys have been reported [17,30,29,32]; however,in the present study we observed substitution mutations at Tyr568Ser, Thr574Pro, Gln575His, Tyr578Pro,Asp579His, His580Gln, Arg586Thr, Asn587Asp andArg588Met which have not been previously reported.We also detected 4 novel point mutations—Ile563Lys,Val569Leu, Tyr570Ser, and Pro577Ser—at codons 563,569, 570 and 577 respectively in exon 11 of the c-kit genewhich have not been previously reported in any neoplasiapatients. The mutations in exon 11 of the c-kit geneobserved in the present study between codons 550 and591 are in agreement with previously reported mutationsin different populations (Figure 2 and Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study heterogeneouspoint mutations in AML patients were observed,some of which were and were not previously reported.In 19 of the 31 AML patients 20 point mutations wereobserved; a point mutation at Lys550Asn in 1 patientand at Ile571Leu in 2 other patients were previouslyreported [29-32]. Mutation at codon 582 (Trp582Tyrand Trp582His) was reported by Tae Won Kim et al [30]and Ying-Yong Hou et al [17] reported Trp582Try andTrp582Gln; however, in 3 of the present studied patientsthere was a different substitution in the same codon inwhich tryptophan was replaced by serine (Trp582Ser).Mutations at codons Tyr568Asp, Ile571Thr, Thr574Tyr,Gln575Ile, Tyr578Phe, Asp579Gln, Asp579Pro,His580Leu, His580Tyr, His580Pro, Arg586Trp,Arg586Ile, Arg586Phe, Arg586Asp, Asn587Glu,Asn587Pro, Asn587His and Arg588Phe, Arg588Tyr, andArg588Lys have been reported [17,30,29,32]; however,in the present study we observed substitution mutations at Tyr568Ser, Thr574Pro, Gln575His, Tyr578Pro,Asp579His, His580Gln, Arg586Thr, Asn587Asp andArg588Met which have not been previously reported.We also detected 4 novel point mutations—Ile563Lys,Val569Leu, Tyr570Ser, and Pro577Ser—at codons 563,569, 570 and 577 respectively in exon 11 of the c-kit genewhich have not been previously reported in any neoplasiapatients. The mutations in exon 11 of the c-kit geneobserved in the present study between codons 550 and591 are in agreement with previously reported mutationsin different populations (Figure 2 and Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In this review its role is dealt with reference to gastrointestinal stromal tumors (GIST) which is a type of gastrointestinal mesenchymal tumors. Gastrointestinal mesenchymal tumors are roughly classified as GIST, showing no evident differentiation from smooth muscle and nervous tissue; myogenic tumors, showing clear differentiation from smooth muscle-leiomyomas mostly and leiomyosarcomas sometimes; and neurogenic tumors, showing clear differentiation from nervous tissue (mostly schwannomas) (Yasuoka et al, 2003). GIST is the most common mesenchymal tumor of the human gastrointestinal tract.…”
Section: C-kit and Gastrointestinal Stromal Tumor (Gist)mentioning
confidence: 99%
“…These are intragenic deletion without affecting the reading frame (Hirota et al, 1998., Lasota et al, 1999; insertion mutation without affecting the reading frame ; and missense mutation , Hirota et al, 1998., Yasuoka et al, 2003. Hirota et al (1998) reported gain of function mutations in 5 out of 6 GISTs studied.…”
Section: C-kit and Gastrointestinal Stromal Tumor (Gist)mentioning
confidence: 99%
See 1 more Smart Citation
“…[146,160,161] Complete understanding of the antiangiogenic mechanisms of KIT is overexpressed and correlates with low survival rates and NK4 may advance the design of novel inhibitors targeting neovas-resistance to chemotherapy in patients with small-cell lung cancer culature. [176,177] MET antisense sequence under the control of the U6 promoter. [175] Finally, KIT expression is MET provides protection from metastasis of human prostate can-an indicator for poor prognosis in a variety of human malignancer cells.…”
Section: Met As a Therapeutic Target 231 Molecular Mechanisms In Camentioning
confidence: 99%